Pengembangan Bahan Ajar Matematika Berbasis Realistic Mathematics Education Untuk Membangun Pemahaman Konsep Matematika Siswa SD - Rike Nurcahyansi (Universitas Bengkulu, 2023)
This study aims to produce mathematics teaching materials using theapproach Realistic Mathematics Education (RME)to build an understanding of the fourth grade mathematics concept in elementary schools as a reference material for students. This study Research and Development (R & D) modifies the ADDIE model. In this research, only up to thestage Deveploment (Development). Validation is carried out by material experts, design experts, and linguists. Teaching materials products that have been validated are given to fourth grade teachers of SD Negeri Bengkulu City to get responses. There are two data analysis techniques in this study, namely qualitative descriptive statistical analysis of input, comments, and suggestions from expert validation sheets and teacher response questionnaires, and analysis. descriptive statistics on scores from the results of expert validation and teacher responses. This study produces mathematics teaching materials based on Realistic Mathematics Education (RME) to build an understanding of mathematical concepts with expert validation assessments of 93.74 with very valid categories, design expert validation of 95 in very valid category, validation of linguists of 89.28 with very valid category, and teacher responses of 89 with very valid category as the final product of development. The conclusion of this research is that the product of developing mathematics teaching materials based on Realistic Mathematics Education is valid and suitable to be used to build an understanding of mathematics concepts in grade IV elementary schools.